Construction of "One Syndrome and One Product" Traditional Chinese Medicine nursing service in the specialized spine department (脊柱专科“一证一品”中医特色护理服务品牌建设思路) - AN Ying (安影); HAO Juntao (郝俊涛); GAO Xinxia (高新霞); XU Huirong (许慧荣); JIANG Tingjie (姜婷杰); JIA Xin (贾昕) (中西医结合护理)
This paper explored the the method, path and content of "One Syndrome and One Product" Traditional Chinese Medicine (TCM) nursing service in the specialized spine department, and summarized the construction and practice of "One Syndrome and One Product" nursing plan. The nursing plan consisted of several important steps as follows: establishing standardized nurse etiquette and service behavior; creating the clinical ward with comfort and warm surroundings; carrying out preparation services for discharged patients; improving nursing service experience to satisfy patients; Strengthening basic nursing and creating a humanistic care service model for patients. Taking low back pain with blood-stasis and Qi-stagnation syndrome as an example, syndrome differentiation nursing was carried out and related TCM nursing program was optimized. Implementation of "One Syndrome and One Product" nursing plan was associate with a continued increase of patient satisfaction, establishment of a humanistic care service model, transformation of nurses’ service concepts, and the formation of caring culture in the department. Through the development of syndrome differentiation nursing, an optimized TCM nursing program with low back pain of blood-stasis and Qi-stagnation syndrome was formed. (探讨脊柱专科“一证一品”中医特色护理服务品牌建设的方法、路径和内容, 构建并实施“一证一品”护理方案。通过建立规范护士礼仪和服务行为; 打造温馨病房; 开展出院患者准备服务; 改善护理服务体验让患者满意; 加强基础护理, 建立科室关爱文化, 为患者打造人文关怀的服务模式。以腰痛病血瘀气滞证为例开展辨证施护, 优化中医护理方案。“一证一品”护理方案的实施有效提升了患者的满意度。通过建立人文关怀服务模式, 转变护士的服务理念, 形成了良好的科室关爱文化。通过开展辨证施护, 形成以腰痛病血瘀气滞证为主的优化中医护理方案。)